'The New Order of Things': Leopardi and AI. - Arnaldi, Marta (Italianist, 2025)
This article positions the writing of nineteenth-century poet and philosopher Giacomo Leopardi next to the universe of artificial intelligence (AI). By using Leopardi's writing as a prism — that is, as a critical object emanating projections, shadows, spectres, and perhaps even ghosts of the future by which the poet himself was haunted — this study reveals some of the ways in which Leopardi's oeuvre has contributed to the history of imaginative thinking about intelligent machines in the Italian-speaking context. Notably, this analysis underscores three key moments of proximity between Leopardi's writing and AI — language, analogical thinking, and emotional intelligence — pointing to novel, interdisciplinary ways of interrogating ideas of the other-than-human in these apparently distant domains. Methodologically, the article evaluates the potential and limitations of bringing into dialogue Leopardi scholarship and AI studies, reflecting on Italian literature's capacity to imagine, inform, and at times induce technological change across historical, cultural, and affective ecosystems.